Evaluation of the Performances of Economic Entities under the Impact of the Accounting Model: Array - Danescu, Magdalena (Acta Universitatis Danubius. Œconomica, 2021)
The accounting model has an important role through the influence in the adoption of decisions that involve planning, solving difficulties, evaluation, action orientation, control and audit. The accounting model realizes the connection between the economic activities and the decisional factors, the primary data regarding the economic activities appearing as an input in the accounting system, and the processed information, necessary for the management represents the output. At both the microeconomic and macroeconomic levels, there is a growing demand for accounting information, which is managed through the accounting model.